STRATEGI DAN TANTANGAN MANAJEMEN PENDIDIKAN ISLAM BERBASIS KEARIFAN LOKAL DI PONDOK PESANTREN - Widodo, Wahyudi (CENDEKIA: JURNAL ILMIAH PENDIDIKAN, 2025)
The research method used is library research with data sources of books, magazines, journals, tafsir and others. The analysis used B Miles and Huberman. The results of the study show that: 1) Educational management strategies based on local wisdom, namely: curriculum development that integrates local wisdom, community involvement and local cultural groups. 2) The model of Islamic education tradition based on local wisdom in pesantren includes: the tradition of Surau Education where people who want to learn must come to the place like a school, the tradition of Sorongan Education where students practice independently to mature their skills by meeting face-to-face with ustadz, and Badongan, a tradition of learning activities that are an approach that prioritizes collective service In studying classical books. 3) There are two challenges in integrating local wisdom into Islamic education management, namely: the gap between the value of local wisdom and Islamic teachings and the limited resources and capacity of ustadz. 4) There are four recommendations for the development of local wisdom-based education management strategies, namely: strengthening the capacity of ustadz in integrating local wisdom, closer collaboration with the community, periodic evaluation and adjustment of management strategies, and the formulation of policies that support